2020
DOI: 10.3389/fped.2020.607506
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Management of Cholestasis Associated With Congenital Syphilis

Abstract: Cholestasis is a rare but life-threatening complication of congenital syphilis. However, standard management methods for this disease have not been established. Here, we report a case of congenital syphilis presenting with progressively worsening cholestasis, and we review the clinical features and management practices. In these cases, differentiation from other diseases presenting with cholestasis during the neonatal period, such as biliary atresia, is critical. In this regard, operative cholangiogram and his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(12 reference statements)
0
3
0
Order By: Relevance
“…The infant's syphilis RPR titre was eight times higher than that of the mother, which is not uncommon and is due to selective transfer of IgG antibodies across the placenta. Liver involvement with raised liver enzymes is common in congenital syphilis 1,2 . A lumbar puncture was normal, excluding congenital neurosyphilis.…”
Section: Answermentioning
confidence: 98%
“…The infant's syphilis RPR titre was eight times higher than that of the mother, which is not uncommon and is due to selective transfer of IgG antibodies across the placenta. Liver involvement with raised liver enzymes is common in congenital syphilis 1,2 . A lumbar puncture was normal, excluding congenital neurosyphilis.…”
Section: Answermentioning
confidence: 98%
“…In the current research, Doppler ultrasonography showed in one baby hepatosplenomegaly and in another splenomegaly, but all had homogeneous liver texture and normal Doppler. Moderate enlargement of the liver with heterogeneous texture and no visualization of the peripheral portal venous vasculature was observed in a case report of syphilitic hepatitis (OGAWA et al, 2020). Doppler abdominal ultrasonography can be performed in the investigation and follow-up of patients with cholestasis, being effective in demonstrating masses, size, change in liver texture, presence of extrahepatic malformations, among others (PINTO; SILVEIRA, 2016).…”
Section: • 98 •mentioning
confidence: 99%
“…Due to the increasing number of cases of CS in the world, knowledge of the effects of cholestasis and its relationship to liver function in children with syphilis is becoming increasingly relevant. More research is needed to establish protocols that identify severe cases early and determine effective treatments for these patients diagnosed with congenital syphilitic hepatitis (OGAWA et al, 2020). According to Brazil (2022), if the penicillin dose is delayed by one day, the treatment must be restarted and the VDRL must be repeated monthly in pregnant women with syphilis because 14% of them may present therapeutic failure, in addition to the risk of reinfection.…”
Section: • 98 •mentioning
confidence: 99%